If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + x * x = 16 Multiply x * x x + x2 = 16 Solving x + x2 = 16 Solving for variable 'x'. Reorder the terms: -16 + x + x2 = 16 + -16 Combine like terms: 16 + -16 = 0 -16 + x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '16' to each side of the equation. -16 + x + 16 + x2 = 0 + 16 Reorder the terms: -16 + 16 + x + x2 = 0 + 16 Combine like terms: -16 + 16 = 0 0 + x + x2 = 0 + 16 x + x2 = 0 + 16 Combine like terms: 0 + 16 = 16 x + x2 = 16 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. x + 0.25 + x2 = 16 + 0.25 Reorder the terms: 0.25 + x + x2 = 16 + 0.25 Combine like terms: 16 + 0.25 = 16.25 0.25 + x + x2 = 16.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 16.25 Calculate the square root of the right side: 4.031128874 Break this problem into two subproblems by setting (x + 0.5) equal to 4.031128874 and -4.031128874.Subproblem 1
x + 0.5 = 4.031128874 Simplifying x + 0.5 = 4.031128874 Reorder the terms: 0.5 + x = 4.031128874 Solving 0.5 + x = 4.031128874 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 4.031128874 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 4.031128874 + -0.5 x = 4.031128874 + -0.5 Combine like terms: 4.031128874 + -0.5 = 3.531128874 x = 3.531128874 Simplifying x = 3.531128874Subproblem 2
x + 0.5 = -4.031128874 Simplifying x + 0.5 = -4.031128874 Reorder the terms: 0.5 + x = -4.031128874 Solving 0.5 + x = -4.031128874 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -4.031128874 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -4.031128874 + -0.5 x = -4.031128874 + -0.5 Combine like terms: -4.031128874 + -0.5 = -4.531128874 x = -4.531128874 Simplifying x = -4.531128874Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.531128874, -4.531128874}
| -46=3x+7y | | x/9-5/6=4x/9 | | (X-17.7)+19.6=28.8 | | 3-2a=15 | | 7(10x+8)=-364 | | 4y+4-3y=2y-6 | | f(x)=4x^2+6x+3 | | r/3-3/8/r=-3/4 | | 6y+2(3x+5)+2y+3= | | 5(x-3)=4x-9+3x | | 5a+b=2 | | (5.6*10^-6)/(7*10^3)= | | -7x-4(5x-2)=197 | | 3x-3(x+1)=e | | 5.6*10^-6/7*10^3= | | 14x-17=6x-10 | | 5.6X10^-6/7X10^3= | | h^2+9h+8=0 | | sin^2xcos^2x=1-cos4x/8 | | 5(a-2)=3(a+1) | | 4y-25=35 | | 2mi=ft | | -2x+7y+-7y=0+-7y | | 4x-16=10x+8 | | 25-(-p+18)=45 | | 120=5x+5(-3x+10) | | 360-59-90-19x= | | 1 = z4– 3 | | h^2-14h+24=0 | | x^2+15x-8=8 | | 2(4x+7)+x= | | 4x-14=42x |